A Novel Saccadic Strategy Revealed by Suppression Head Impulse Testing of Patients with Bilateral Vestibular Loss - de Waele, Catherine; Shen, Qiwen; Magnani, Christophe; Curthoys, Ian S. (Frontiers in Neurology, 2017)
Objective We examined the eye movement response patterns of a group of patients with bilateral vestibular loss (BVL) during suppression head impulse testing. Some showed a new saccadic strategy which may have potential for explaining how patients use saccades to recover from vestibular loss. Methods Eight patients with severe bilateral vestibular loss (VOR gains less than 0.35 and absent otolithic function) were tested. All patients were given the Dizziness Handicap Inventory (DHI) and questioned about oscillopsia during abrupt head movements. Two paradigms of video head impulse testing of the horizontal VOR were used: 1) the classical head impulse paradigm (called HIMPs) – fixating an earth fixed target during the head impulse, and 2) the new complementary test paradigm –fixating a head-fixed target during the head impulse (called SHIMPs). The VOR gain of HIMPs was quantified by two algorithms. Results During SHIMPs testing some BVL patients consistently generated an inappropriate covert compensatory saccade during the head impulse which required a corresponding large anti-compensatory saccade at the end of the head impulse in order to obey the instructions to maintain gaze on the head-fixed target. In contrast, other BVL patients did not generate this inappropriate covert saccade and did not exhibit a corresponding anti-compensatory saccade. The latencies of the covert saccade in SHIMPs and HIMPs were similar. Conclusion The pattern of covert saccades during SHIMPs appears to be related to the reduction of oscillopsia during abrupt head movements. BVL patients who did not report oscillopsia showed this unusual saccadic pattern, whereas BVL patients who reported oscillopsia did not show this pattern. This inappropriate covert SHIMPs saccade may be an objective indicator of how some patients with vestibular loss have learned to trigger covert saccades during head movements in everyday life.